Prediction of Safe Life of Propellants - Singh, Harihar (Defence Science Journal, 2014)
A mathematical formula has been derived to assess the safe life of propellants based on the rate of decomposition of nitric esters and action of stabilizers on the decomposition products of the nitric ester constituents of the propellants.